Experimental Investigation of Milling Stability based on a Method for Stability Prediction - Zhang Kaifei; Jin Gang (Jixie chuandong)
Aiming at the problem of chatter vibration during milling,a new method for solving multiple time delays system is presented to predict the stability in the process of milling cutter. A comparison with prior methods is conducted to verify the accuracy and efficiency of proposed approach for the stability prediction. By using the variable pitch cutter,the experiment of milling stability is carried out. According to the obtained predicted results,the multiple sets milling parameters are selected for the milling experiment,a consistency between the experimental data and theory study is studied. The experimental results show that the proposed method has a better predictive ability than the prior methods.